The Synechocystis sp. PCC 6803 Genome Encodes Up to Four 2-Phosphoglycolate Phosphatases - Rai, Snigdha; Lucius, Stefan; Kern, Ramona; Bauwe, Hermann; Kaplan, Aaron; Kopka, Joachim; Hagemann, Martin (Frontiers in Plant Science, 2018)
Photorespiratory phosphoglycolate (2PG) metabolism is essential for cyanobacteria, algae, and plants. The first enzyme of the pathway, 2PG phosphatase (PGPase), is known from plants and algae but was scarcely investigated in cyanobacteria. In silico analysis revealed four candidate genes (slr0458, slr0586, sll1349 and slr1762I) in the genome of the model cyanobacterium Synechocystis sp. PCC 6803 that all belong to the 2-haloacid dehalogenase (HAD) superfamily and could possibly encode PGPase proteins. However, in contrast to known algal and plant PGPases, the putative cyanobacterial PGPases belong to another HAD subfamily implying that PGPases in eukaryotic phototrophs did not originate from cyanobacterial PGPases. To verify their function, these four genes were inactivated both individually and in combination. A mild high-CO2-requiring (HCR) growth phenotype typical for photorespiratory mutants was observed only in ∆sll1349. Combinatorial inactivation enhanced the HCR phenotype in specific double and triple mutants. Heterologous expression of the putative cyanobacterial PGPases in E. coli led to higher PGPase activities in crude cell extracts, but only the purified Slr0458 protein showed PGPase activity. Hence, we propose that a consortium of up to four photorespiratory PGPases may initiate photorespiratory 2PG metabolism in Synechocystis. We suggest that redundancy of this essential enzyme activity could be related to the highly adaptive lifestyle of cyanobacteria such as Synechocystis sp. PCC 6803, which allows them to grow under very diverse conditions.